Corruption Eradication in Indonesia: The Experience of The Corruption Eradication Commission (KPK) - Leo Agustino; Indah Fitriani; Harits Hijrah Wicaksana; Ahmad Daelami (Journal of Governance, 2021)
The focus of this paper is on the discussion and analysis of corruption eradication attempts in Indonesia with the Komisi Pemberantasan Korupsi (KPK), The Corruption Eradication Commission) as its centre. As an activity, the commencement of the corruption eradication dates to the pre-Reformation Era. However, its presence is mainly in the form of the foundation of the anti-corruption body without playing real roles as a nominal anti-corruption institution. As a response towards pressure from the IMF, in 2002 the Corruption Eradication Commission was formed as a specialized institution to tackle chronic corruption issues strangling Indonesia in the era of Soeharto’s New Order. Unfortunately, since its inception, there has been no president who is committed to the eradication attempts and therefore sided with the KPK. It is due to the commission’s huge constitutional power (investigation, probing, tapping, arrest, and prosecution) and hence these frighten many corrupt officials. Numerous political elites have been arrested by the KPK such as ministers, governors, regents, mayors and law-enforcers top officials. Consequently, unsurprisingly the KPK faces multi-directional attacks attempting at its weakening through the arrests of its top leaders, iterating its ad-hock (can be dissolved at any time.) status, and the revision of KPK law. Therefore, the government should act firmly to provide protection and supports to the KPK against those potential threats aiming at weakening the commission, to block any legislation potentially lessening the functions of the KPK, and to make sure both KPK’s top leaderships and average personnel are impartial and free of vested interests.